Assessing the effectiveness of the SOLIO Alfa Cure Plus device in treating low back pain: a randomized controlled study - Hadari Yotam; Pesah Galia; Goor-Aryeh Itay; Ungar Lior (Journal of Orthopaedic Surgery and Research)
Abstract Background Nonspecific low back pain (LBP) has become a significant worldwide public health problem. It is estimated that 84% of people present it at some point in their lives, in which 23% experience its chronic form, negatively affecting their daily lives. Because pain management tool that doesn’t require a firm diagnosis, the development of a device, as SOLIO Alfa Cure Plus, that emanates low level laser therapy, radio frequency and heat with the goal of easing chronic back pain was highly expected. Methods randomized, single blinded, controlled trial. Measures: Numeric Pain Rating Scale (NPRS), the Oswestry Disability Index (ODI) and the Schober’s test. Thirty-seven patients completed pain, disability, and lower back flexibility scales. Randomization was obtained by having an equal amount of sham and real devices and distributing them randomly to patients out of a box where the devices were. Results We observed a larger pain relief in the SOLIO group (42% vs. 23% p = 0.03), and a higher improvement in flexibility (13%) compared to a worsening in the sham group (6.5%; p = 0.04). Conclusion We concluded that utilizing the SOLIO Alfa Cure Plus device may dramatically reduce back pain and allow patients to experience an improvement in quality of life as a result. Trial registration: The clinical trials registration is 8475-21-SMC.